Exfoliated 2D Antimonene‐Based Structures for Light‐Harvesting Photoactive Layer of Highly Stable Solar Cells. Issue 6 (5th April 2022) - Bat-Erdene, Munkhjargal; Myagmarsereejid, Purevlkham; Bati, Abdulaziz S. R.; Qin, Jiadong; Zhong, Yu Lin; Shapter, Joseph G.; Batmunkh, Munkhbayar
Abstract : 2D materials have shown great promise in various applications including solar cells, but their use as light‐harvesting active layers in photovoltaic (PV) devices is limited. Herein, surface‐oxidized antimonene sheets are prepared using a liquid‐phase exfoliation method and employed as an active light absorber material after functionalization. It is shown that 2D antimonene possesses unique surface chemistry that allows it to form photoactive Sb2 S3 light absorbers for solar cells under ambient conditions. Under the standard PV testing conditions (AM1.5G), devices fabricated with 2D antimonene‐based light‐harvesting materials deliver a power conversion efficiency (PCE) of up to 4.28%. This novel type of solar cell exhibits outstanding operational stabilities, preserving >90% of the initial PCE after aging for 60 min at a temperature of 85 °C, retaining >95% of the initial efficiency after exposure to continuous light illumination under 1 sun for 180 min, and maintaining its functionality after being underwater for 25 min. This work opens new avenues for research in 2D materials and photovoltaics. Abstract : For the first time, surface‐oxidized antimonene (Sb) sheets are synthesized using a liquid‐phase exfoliation method for use as a photoactive active light absorber material after functionalization. The fabricated devices exhibit promising photovoltaic efficiencies of up to 4.28% with excellent reproducibility. This new class of solar cells fabricated based on 2D Sb flakes shows outstanding operational stabilities.